Analisis Tingkat Kepuasan Konsumen Terhadap Pelayanan PT Perintis Perlindungan Instalasi Listrik Nasional (PPILN) Area Berau - Meiriana, Yuyun (FAKULTAS EKONOMI DAN BISNIS UNIKARTA, 2019)
Abstract:This study has objective to determine the level of customer satisfaction to the public ppiln pt berau area in terms of service quality dimensions consisting reliability, responsiveness assurance emphaty, and tangible. Took samples from 100 were taken proportionally sampling method purposive random sampling. While a test hypotheses using the chi square, the t-test and analysis using importance-performance analysis.Keywords: Consumen Satisfaction, Service